Roles of Mesenchymal Stem Cell-derived Extracellular Vesicles in Cancer: Development and Target Therapy - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2025)
Extracellular vesicles (EVs) are membrane structures that enclose proteins, lipids, RNAs, metabolites, growth factors, and cytokines. EVs derived from mesenchymal stem cells (MSCs) can either stimulate or inhibit tumor growth in various malignancies through paracrine signaling. Tumor-associated MSCs (TA-MSCs), often described as